Pengembangan MONOLI (Monopoli Lingkungan) Berbantu Teknologi QR Code Untuk Meningkatkan Kemampuan Literasi Sains Siswa Pada Materi Pencemaran Lingkungan - Ali Ahmatul Umri Hasibuan (Jurnal Biologi dan Pembelajarannya (JB&P), 2024)
This study aims to develop and evaluate the “Environmental Monopoly” learning media based on QR Code technology to enhance students’ science literacy on environmental pollution material. The methods used include validation by subject matter experts and education practitioners, as well as feasibility testing with students. The results indicate that this media has good feasibility with validation scores of 72.5% for content feasibility, 75% for presentation, and 68.75% for language. Trials in seventh-grade classes showed that 92% of students felt more active, 85% showed improved understanding of the material, and 88% expressed satisfaction with the use of this media. These results suggest that “Environmental Monopoly” can be an effective and innovative learning tool to improve students’ science literacy.